IMMUNO-MODULATORY PROPERTIES OF PREBIOTICS EXTRACTED FROM Vernonia amygdalina - Ezeonu, I.M.; Asuquo, A.E.; Ukwah, B.N.; Ukoha, P.O. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Vernonia amygdalina, commonly called bitter-leaf, is widely consumed in many parts of Africa, and Nigeria, inparticular. The leaf extract has been reported to have antimicrobial, anti-plasmodial, anti-helminthic, as well as prebiotic properties,but its immuno-modulatory effects have not been well-studied, neither have the prebiotics been identified. This study evaluated theimmuno-modulatory properties of the aqueous leaf extract and identified the prebiotic components.Methods: The immuno-modulatory potential was evaluated by monitoring the effects of oral administration of the extract onimmunological, haematological and lipid profiles of Rattus norvegicus, while the prebiotic components were identified by thin layerchromatography (TLC), following liquid-liquid fractionation of the extract.Results: Consumption of the extract caused significant increases in CD4+-, white blood cell-, total lymphocyte- and high densitylipid (HDL) counts; decreases in low density lipid (LDL) and triglycerides and no significant effect on haemoglobin (Hb) andpacked cell volume (PCV) in the blood of test animals. The water-soluble fraction of the extract contained most of the phytoconstituentsof the extract and Thin Layer Chromatographic analysis of the fraction revealed the presence of fructo-oligosaccharideand galacto-oligosaccharide prebiotics.Conclusion: The results from this study have shown that the aqueous leaf extract of V. amygdalina has positive immune-modulatoryand haematologic effects and contains some important prebiotic compounds.